1986
DOI: 10.1172/jci112577
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of normal membrane stability to unstable protein 4.1-deficient erythrocyte membranes by incorporation of purified protein 4.1.

Abstract: Protein 4.1, a principal component of the erythrocyte membrane skeleton, is thought to be important in regulating membrane stability through its interaction with spectrin and actin. A key role for protein 4.1 has been indicated in studies in which deficiency of this protein was shown to result in marked instability of the membrane. In order to obtain direct evidence for the functional role of protein 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 32 publications
1
73
0
Order By: Relevance
“…This hypothesis assumes that only a subpopulation of protein 4.1 regulates SSPC at the plasma membrane. The remaining protein 4.1 may independently regulate properties such as membrane deformability, which is restored by the addition of exogenous protein 4.1 in the absence of either p55 or hDlg (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis assumes that only a subpopulation of protein 4.1 regulates SSPC at the plasma membrane. The remaining protein 4.1 may independently regulate properties such as membrane deformability, which is restored by the addition of exogenous protein 4.1 in the absence of either p55 or hDlg (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…By interacting with components of the spectrin-based membrane skeleton, as well as with integral proteins in the overlying lipid bilayer, 4.1R is critical to both the structural integrity of the skeleton and its attachment to the membrane. Deficiency of 4.1R results in red cells with morphological abnormalities and unstable membranes due to the assembly of a mechanically compromised membrane skeleton (1,2). Such defects are manifested by the appearance of circulating cells with elliptical morphology and also by the presence of fragmented cells due to the decreased membrane mechanical stability.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al (1999) reported that erythrocytes from 4.1R-knockout mice demonstrate membrane instability and reduced levels of other cytoskeletal proteins, consequently leading to hemolytic anemia. In addition, Stagg (Takakuwa et al, 1986;Mohler et al, 2004;Baines et al, 2009) showed that electrocardiographic analysis revealed diminished heart rate with a prolonged Q-T interval and reduction of the Na + /Ca 2+ exchanger current density in 4.1R-deficient (knockout) mice. However, no changes regarding the ejection fraction or fractional shortening have been observed in 4.1R-deficient mice, as assessed by echocardiography (Stagg et al, 2008).…”
Section: Discussionmentioning
confidence: 99%